Hubungan Keaktifan dan Minat Belajar Siswa Terhadap Pelajaran Matematika Untuk Meningkatkan Prestasi Siswa SD - Ma’alya Nakhlah, Riya; Syifa’ul Azhar; Mudrikatunnisa’ Mudrikatunnisa’; Ryan Prayogo; Fitriyah Amaliyah (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
Educational learning achievement is needed to determine the success rate of student learning. Student learning interest has a significant influence on student learning outcomes. This research was conducted to determine the relationship between learning activeness and interest in learning mathematics on mathematics learning achievement. The method used in this study is a survey method with multiple linear regression analysis. Based on the variables of activeness and interest in learning obtained from questionnaires or questionnaires with a total of 18 statements with 26 respondents showing the results of the prerequisite analysis test or assumption test and the results of hypothesis testing. The results of this study are based on a multiple linear regression test of 0.627 or equal to 62.7%. This figure means that the activeness and interest in learning simultaneously (together) affect the mathematics achievement of elementary school students by 62.7%.